Religious Character Building in SMIT Daarul Qur'an South Tangerang - Nurlaili, Lili (Pusat Publikasi Nusantara, 2023)
Presidential Regulation Number 87 of 2017 concerning Strengthening Character Education is one of the efforts made by the Indonesian government as a cultured nation and upholding noble morals, realizing religious ethics, noble values, wisdom, and ethics in accordance with the noble ideals of the nation. the founding father of Indonesia. The realization of all these things is a shared responsibility between families, education units, and communities. The Presidential Decree is about Strengthening Character Education (PPK), which is an educational movement that is the responsibility of education units to strengthen the character of students through harmonization of the heart, training of feelings, thoughts and sports with involvement and cooperation between educational units. family and community as part of the National Movement for Mental Revolution (GNRM). To obtain the expected goals in this study, it is necessary to set research objectives. The objectives developed from the above problem formulation are: 1) To describe the concept of religious character formation in SMIT Daarul Qur'an Tangsel? 2) To describe the factors supporting the formation of religious character in SMIT Daarul Qur'an Tangsel? 3) To describe the inhibiting factors of religious character formation in SMIT Daarul Qur'an Tangsel? This research is expected to be useful not only for SMAIT Daarul Qur'an but also for the wider community